An Hybrid Digital-Analog Sliding Mode Controller for Photovoltaic Applications - Mamarelis, E.; Petrone, G.; Spagnuolo, G. (IEEE transactions on industrial informatics, 2013)
Sliding mode is a control technique that is widely employed in switching converter applications. Such a nonlinear control technique, which is commonly implemented by means of analog circuitry only, forces the switches commutations by comparing a reference signal with a combination of signals acquired on the converter itself. In this way, the control action and the switching modulation are integrated in a single functional block. In this paper the implementation of the sliding mode controller in a low cost digital device is discussed. The proposed approach profits from features offered by some digital devices, e.g., the dsPic33FJ16GS502 family from Microchip Technology Inc., in order to make the implementation simple. In the paper, the aspects related to the accuracy of the comparison between the signals required by the sliding mode controller are discussed. Moreover, the elaboration time needed to calculate the signals that drive the converter's switching devices is the subject of an in-depth analysis. The techniques proposed in the paper have been validated by means of simulations and through experimental results performed on a switching dc/dc converter for photovoltaic applications.